PENGUJIAN PERFORMA REAKTOR DOWNDRAFT BIOMASSA KOTORAN SAPI - Muhammad Ridwan Ridwan; Noviyanti Nugraha Nugraha (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
Biomass power plants are electricity generators with alternative energy that utilize organicmaterials, in this case cow dung. The cow dung is then processed to produce syngas. Syngas is used as fuelto turn turbines. In previous studies, a cow manure gasification reactor was designed and manufactured.This reactor is part of a biomass power plant system (PLTBm) which is made separately. The power outputtarget of this PLTBm is 370 kW. The purpose of this study was to examine the performance of the downdraftreactor of cow dung biomass, namely discharge, temperature, and analyze the gas content released by thereactor so that the power that can be generated by the reactor can be obtained. The test results obtained acombustion chamber temperature of 580°C and a discharge of 0.285 m3/s. The composition of the outputgas is acetylene 58.16%, hexane 27.66%, butane 6.38%, and methane 7.8%. From the calculation results,the power generated by the reactor is 342 kW.